Brain drain and development traps - Jean-Pascal Bénassy; Elise S. Brézis (Bar-Ilan University, Department of Economics, 2011)
This paper links the two fields of 'development traps' and 'brain drain'. We construct a model which integrates endogenous international migration into a simple growth model. As a result the dynamics of the economy can feature some underdevelopment traps: an economy starting with a low level of human capital can be caught in a vicious circle where low level of human capital leads to low wages, and low wages leads to emigration of valuable human capital. We also show that our model displays a rich array of different dynamic regimes, including the above traps, but other regimes as well, and we link explicitly the nature of the regimes to technology and policy parameters.
Keywords: F22; J61; O11; O15; 330; brain drain; development traps; human capital; migration; Brain Drain; Humankapital; Internationale Wanderung; Unterentwicklung; Wachstumstheorie